A double time-scale passenger assignment model for high-speed railway networks with continuum capacity approximation. (June 2021) - Xu, Guangming; Liu, Wei; Wu, Runfa; Yang, Hai
Highlights: This study predicts the time-and-space-dependent flow for high-speed rail network. The passenger flow pattern is ticket-booking-time-dependent. An algorithm is designed for solving the passenger flow assignment model. The model and algorithm are applied on the large-scale rail network of China. Abstract: This study models spatiotemporal passenger flow distribution for high-speed railway (HSR) networks with capacity constraints. The HSR travel demand involves two time-dimensions, i.e., the ticket booking time and the desired departure time. Under the principle of first-booked-first-served, a passenger flow assignment model is formulated, where a later ticket booking time may result in less available travel options. A solution algorithm is then designed for solving the ticket-booking-time-dependent assignment model. The model is tested and illustrated with two numerical examples: a toy network example and a large-scale Chinese HSR network example.